2020
DOI: 10.18295/squmj.2020.20.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Breast Cancer Risk Factors, Symptoms and Breast Self-Examination Among Omani Female Teachers: A cross-sectional study

Abstract: Objectives: This study aimed to assess knowledge of breast cancer (BC) risk factors, warning signs and symptoms and breast self-examination (BSE) practice among Omani female teachers in Al-Dhahira Governorate. Methods: A cross-sectional sample of female teachers aged 20–50 years was collected from January to December 2018 from three wilayats (provinces) in Al-Dhahira—Ibri, Dhank and Yunqal. A questionnaire that included the Breast Cancer Awareness Scale and demographic characteristics was administered. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This model was determined a priori on the basis of previous studies. 18,19,[36][37][38][39][40][41] Results of the bivariable logistic regression analyses are provided in Appendix Tables A1-A4.…”
Section: Knowledge Generatedmentioning
confidence: 99%
“…This model was determined a priori on the basis of previous studies. 18,19,[36][37][38][39][40][41] Results of the bivariable logistic regression analyses are provided in Appendix Tables A1-A4.…”
Section: Knowledge Generatedmentioning
confidence: 99%
“… 28 Donnelly et al 29 described that only 28.9% of the Arab females in Qatar are aware of BC screening practices, and less than one-third of them actually practiced BC screening. Al-Ismaili et al 30 found only 60.5% of Omani teachers to possess a good overall knowledge about BC, and only 57% practicing breast screening examination.…”
mentioning
confidence: 99%
“…Literature on male breast cancer awareness is limited. Awareness studies generally focused on male high school students ( Al-Amoudi et al, 2016 ), female teachers ( Al-Ismaili et al, 2020 ), migrant agricultural workers ( Furgurson et al, 2019 ), nursing students ( Yakar et al, 2021 ), women, and men ( Alsowiyan et al, 2020 ; Farsi et al, 2020 ), yet all these studies questioned breast cancer regardless of gender.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the second most common cancer worldwide ( Al-Ismaili et al, 2020 ). Its incidence and mortality rates have been increasing mostly in developing countries including Turkey ( Özmen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%